SARS-CoV-2 clearance in COVID-19 patients with Novaferon treatment: A randomized, open-label, parallel-group trial (2020)
Background: The antiviral effects of Novaferon, a potent antiviral protein drug, on COVID-19 was evaluated in the laboratory, and in a randomized, open-label, parallel-group trial. Methods: In the laboratory, Novaferon's inhibition of viral replication in cells infected with SARS-CoV-2, and prevention of SARS-CoV-2 entry into healthy cells was determined. Antiviral effects of Novaferon in COVID-19 patients with treatment of Novaferon, Novaferon plus Lopinavir/Ritonavir, or Lopinavir/ Ritonavir were evaluated. The primary endpoint was the SARS-CoV-2 clearance rates on day six of treatment, and the secondary endpoint was the time to SARS-CoV-2 clearance. Results: Novaferon inhibited viral replication (EC50 = 1.02 ng/ml), and prevented viral infection (EC50 = 0.10 ng/ml). Results from the 89 enrolled COVID-19 patients showed that both Novaferon and Novaferon plus Lopinavir/Ritonavir groups had significantly higher viral clearance rates on day six than Lopinavir/ Ritonavir group (50.0% vs. 24.1%, p = 0.0400, and 60.0% vs. 24.1%, p = 0.0053). The median time to viral clearance was six days, six days, and nine days for three groups, respectively, a 3-day reduction in both the Novaferon and Novaferon plus Lopinavir/Ritonavir groups compared with the Lopinavir/Ritonavir group. Conclusions: Novaferon exhibited anti-SARS-CoV-2 effects in vitro and in COVID-19 patients. These data justify further evaluation of Novaferon